Bioactive Properties of Mushroom (Agaricus bisporus) Stipe Extracts. Issue 6 (16th March 2015) - Ndungutse, Vedaste; Mereddy, Ram; Sultanbawa, Yasmina
Abstract: The antibacterial activity and total phenolic (TP) content of A garicus bisporus stipes were assessed using solvent and water extracts to determine its bioactivity. Extraction methods included accelerated solvent extraction (ASE) and hot water followed by membrane concentration. Water extract from ASE had the highest TP of 1.08 gallic acid equivalents (GAE)/g dry weight (DW) followed by ethanol at 0.61 mg GAE/g DW and 0.11 mg GAE/g DW for acetone. Acetone extracts inhibited E scherichia coli and S taphylococcus aureus at less than 50%; ethanol inhibited E . coli at 61.9% and S.   aureus at 56.6%; and ASE water inhibited E.   coli at 78.6% and S.   aureus at 65.4%. The TP content of membrane concentrated extract of mushroom was 17 mg GAE in 100 mL. Membrane concentrated water extracts had a higher percentage inhibition on S.   aureus than E.   coli . Overall, the results were promising for further application of mushroom stipe extracts as a functional food additive. Practical Applications: Mushrooms are known for their health benefits and have been identified as a good source of nutrients. The highly perishable nature of mushrooms warrants further processing and preservation to minimize losses along the supply chain. This study explores the possibility of adding value to mushroom stipes, a by‐product of the fresh mushroom industry. The extracts assessed indicate the antibacterial activity and phenolic content, and the potential of using these extracts as functional ingredients in the food industry. This study provides valuable information to the scientific community and to the industries developing novel ingredients to meet the market demand for natural food additives.